Noninvasive assessment of endothelial function and ST segment changes during exercise testing in coronary artery disease - Chequer,G. (2009)
Endothelial function (EF) plays an important role in the onset and clinical course of atherosclerosis, although its relationship with the presence and extent of coronary artery disease (CAD) has not been well defined. We evaluated EF and the ST segment response to an exercise test in patients with a broad spectrum of CAD defined by coronary angiography. Sixty-two patients submitted to diagnostic catheterization for the evaluation of chest pain or ischemia in a provocative test were divided into three groups according to the presence and severity of atherosclerotic lesions (AL): group 1: normal coronaries (N = 19); group 2: CAD with AL <70% (N = 17); group 3: CAD with AL ≥70% (N = 26). EF was evaluated by the percentage of flow-mediated dilatation (%FMD) in the brachial artery during reactive hyperemia induced by occlusion of the forearm with a pneumatic cuff for 5 min. Fifty-four patients were subjected to an exercise test. Gender and age were not significantly correlated with %FMD. EF was markedly reduced in both groups with CAD (76.5 and 73.1% vs 31.6% in group 1) and a higher frequency of ischemic alterations in the ST segment (70.8%) was observed in the group with obstructive CAD with AL ≥70% during the exercise test. Endothelial dysfunction was observed in patients with CAD, irrespective of the severity of injury. A significantly higher frequency of ischemic alterations in the ST segment was observed in the group with obstructive CAD. EF and exercise ECG differed among the three groups and may provide complementary information for the assessment of CAD.